[Papers of] 10th International Conference on Liquefied Natural Gas, the Putra World Trade Centre, Kuala Lumpur, May 25-28, 1992 - 467816 International Conference on Liquefied Natural Gas (10th : 1992 : Kuala Lumpur) (Chicago, Ill. : Institute of Gas Technology, 1992)
51